A Descriptive Study of E-Collection Systems and Municipal Revenue Efficiency: Evidence from Selected Municipalities in Iloilo Province, Philippines - Convocar, Blessed Art Marie L.; Feguro, Marjo F.; Querimit, Rachylle Claryce T.; Solinap, Irish Faith A.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examines the effect of electronic collection (e-collection) systems on municipal revenue efficiency in selected municipalities of Iloilo Province, Philippines, within the context of ongoing digital governance reforms. While prior studies have established that electronic revenue systems generally enhance collection performance, empirical evidence at the municipal level in developing-country settings remains limited, particularly regarding how specific efficiency dimensions such as timeliness, accuracy, cost-effectiveness, and transparency are affected under partial system integration. Using a descriptive quantitative research design, data were collected through structured questionnaires administered to municipal treasurer and accountant offices in municipalities with operational e-collection systems. Revenue efficiency was assessed using a five-point Likert scale and analyzed through frequency distributions, weighted means, and standard deviations. Results indicate that e-collection systems have a high positive effect on revenue efficiency, particularly in transaction timeliness (WM = 3.74), cost-effectiveness (WM = 3.73), and transparency and accountability (WM = 3.96). Respondents reported faster payment processing, reduced manual encoding, clearer audit trails, and improved public trust. However, the impact on delinquency reduction and real-time reconciliation remained moderate, largely due to stand-alone system deployment, limited system integration with accounting platforms, and uneven staff capacity. Despite adoption growth in 2024 with 38.10% of sampled municipalities implementing e-collection, more than 90% of municipalities still process less than 10% of total transactions electronically. The study contributes localized empirical evidence showing that efficiency gains from e-collection are significant but constrained by institutional, technical, and administrative factors.